Evaluation of Dose Derived From HTO for Adults in the Vicinity of Qinshan Nuclear Power Base. Issue 4 (October 2019) - Qin, Lailai; Dai, Zhongqin; Xia, Zhenghai; Ma, Yuhua; Deng, Ke; Liu, Jiayu; Ma, Zhaowei; Zhang, Qin; Yang, Guo; Wei, Fei; Wu, Shengwei; Bao, Guangliang; et al.
Abstract : Abstract: Tritium that is released from nuclear facilities, especially from nuclear reactor units, may be the main origination of tritium in the environment. Atmospheric tritiated water (HTO) is the main chemical form of tritium that is released from nuclear reactor units. HTO in the air, drinking water and foods should be monitored routinely to protect public from the radiological hazards of tritium. Here, concentrations of HTO in the air, drinking water and foods in the vicinity of Qinshan Nuclear Power (QNP) base were measured from 2012 to 2016. And based on the concentrations of HTO measured, annual dose equivalent and collective dose equivalent for adults were calculated to evaluate the radiological hazards derived from HTO. The annual dose equivalent for adults in Qinshan and Wuyuan communities were both far below the dose limit for public exposure, and both showed an increasing trend, indicating that great attention still should be payed to the releasing of tritium from nuclear reactor units in the QNP base.